(untitled) (Academicia Globe: Inderscience Research, 2022)
Melilotus officinalis contained coumarins, melilotin, phenolic acids, flavonoids, steroids, saponins, volatile oils, fats, triterpenes, carbohydrates, sugar, anthraquinone glycosides, mucilage, tannin, bishydroxycoumarin, choline, alcohols, uric acid and many other chemical groups. Antimicrobial, antioxidant, anticancer, anti-inflammatory, neural, protective, sedative, anxiolytic, smooth muscle relaxant, hypotensive and manyother pharmacological effects. The current article highlighted the chemical constituents and pharmacological effects of Melilotus officinalis.